Sin and Education - Andersen, William (Journal of Christian education, 2011)
Sin often becomes lost in our educational discussions about human beings. It is to be distinguished from antisocial behaviour and unfortunate conditioning. It intrudes into the educational process through the student, through the teacher and the via the value system of every culture. Often it is the revelation of holiness that provokes recognition of personal sin, and sometimes also of corporate sin. The organiser of ‘the world’ is Satan himself: a real being. And his helpers include demons, also real beings. The most powerful factor in dealing with sin, in the sphere of education, is the teacher's personal walk with God.